Geotourism aspects of the Lufeng Dinosaur National Geopark in Yunnan Province, China - Daněk, Tomáš; Skupien, Petr (GeoScience Engineering, 2016)
The Lufeng Dinosaur National Geopark in Yunnan province, China is important part of the world geoheritage with the great scientific and aesthetic value. The area has been under scientific research since 1938 when the first dinosaur fossils were discovered here by geologist Bian Meinian and technician Wang Cunyi. Professor Yang announced discovery of new early Jurassic herbivore prosauropod from Lufeng in 1941, which he gave the name Lufengosaurus huenei. In 2004, the area was listed as China`s National Geopark. It was opened for visitors in 2008. Besides the high scientific value the geopark is also important resource for science based and educational tourism. This paper briefly introduces the history of scientific research, the basic geology of the site and the most important fossils discovered here. The main characteristic, geodiversity and geotourism of fossil geoheritage in the area are discussed here.